THE LOGIC OF SCIENTIFIC KNOWLEDGE BY KARL POPPER - Ikrom Jomuradov (European Science Publishing, 2024)
Karl Popper’s contributions to the philosophy of science have profoundly influenced the understanding of scientific methodology and epistemology. This paper explores Popper’s central tenet of falsifiability as the demarcation criterion for scientific theories, contrasting it with verifications. By examining his rejection of inductivism and his advocacy for critical rationalism, the work underscores the logical structure of scientific knowledge as a dynamic and iterative process. Emphasis is placed on the implications of Popper’s ideas for the growth of knowledge, the role of hypotheses, and the problem of induction in scientific inquiry.
Keywords: Falsifiability, Scientific methodology, Critical rationalism, Hypotheses, Induction problem, Demarcation criterion.